India 2025: the public distribution system and National Food Security Act 2013. Issue 2 (17th February 2019) - Chakraborty, Sayan; Sarmah, S. P.
ABSTRACT: The Government of India introduced the National Food Security Act (NFSA) 2013 to strengthen the public distribution system (PDS) in India. Extending the PDS service network is a contentious issue, especially for India's rural regions. This article aims to estimate the level of expansion of the PDS network, additional food grain requirement, and increased storage facilities required to serve the growing population of India up to 2025. The statistical analysis highlights the need for significant changes in the PDS to meet NFSA, and the findings can aid policy-makers to design a more robust PDS.